Status of Melamipsora Rusts on Poplars in India - Singh, Sujan; Khan, S. N.; Misra, B. M. (Indian Forester, 1983)
The paper deals with present status of Melampsora rusts on poplars in India. No exotic rust pathogen bas so for been recorded in nurseries and plantations of exotic poplars in the country. Melampsora ciliata, an indigenous rust attacking Poplur ciliata in nurseries, plantations and natural forests in the Himalayas, has however, been recorded in various clones of Populus deltoides. P alba, P. nigra. P. yunnanensis, P. trichocarpa, and many cultivars of P. x euroamericana. It is suggested that to check inadvertent entry of exotic rust pathogens, a certificate from exporting countries stating that the cuttings have been collected from areas were rust pathogens do not exist should be insisted. To check introduction of M. ciliata in plantations of exotic poplars in plain areas of Uttar Pradesh, Punjab and Haryana States, a restriction should be imposed that no cuttings collected from rust infected localities should be introduced in these areas.